A standard addition method to quantify serum lithium by inductively coupled plasma mass spectrometry. (May 2022) - Fan, Xiaoyu; Li, Qing; Lin, Ping; Jin, Zhonggan; Chen, Meizi; Ju, Yi
Background: Therapeutic monitoring of lithium (Li) is important because of its narrow therapeutic range and therapeutic index. Here, the authors present the evaluation of an accurate method for the determination of lithium in serum. Method: Serum samples were diluted with 0.3% ultrapure nitric acid and were spiked with an internal standard germanium (Ge). The Li/Ge ratio was detected in He mode; we utilized standard addition method to quantify lithium in human serum. The new inductively coupled plasma mass spectrometry (ICP-MS) assay was characterized for linearity, specificity, imprecision, trueness, accuracy, and comparison. Results: The correlation coefficients (r) of linearity were all > 0.9999. The specificity proved to be good. The total coefficients of variation (CV) were 1.11% and 0.49% for the two serum samples. The mean bias from target values of standard reference materials (SRM 956d) was −0.71% for Level I, −017% for Level II, and 2.20 for Level III. External Quality Assessment Scheme for Reference Laboratories in Laboratory Medicine (RELA) gave satisfied results for the new method. Comparison with the ion-selective electrode routine method got reasonable results. Conclusion: This high accuracy method is an attractive alternative for lithium measurement and can be used as a candidate reference method to improve quality of serum lithium in China.